2009
DOI: 10.1359/jbmr.081217
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization and Bone Resorption Are Regulated by the Androgen Receptor in Male Mice

Abstract: Androgens play a key role in skeletal growth and bone maintenance; however, their mechanism of action remains unclear. To address this, we selectively deleted the androgen receptor (AR) in terminally differentiated, mineralizing osteoblasts using the Cre/loxP system in mice (osteocalcin-Cre AR knockouts [mOBL-ARKOs]). Male mOBL-ARKOs had decreased femoral trabecular bone volume compared with littermate controls because of a reduction in trabecular number at 6, 12, and 24 wk of age, indicative of increased bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
93
1
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 50 publications
16
93
1
2
Order By: Relevance
“…Our results in male mice were in line with those of Chiang et al, 19 who also reported a reduction in Tb.BV in male mice with osteoblast-targeted AR inactivation. However, differing from their results, we did not detect significant differences in cortical bone thickness in male mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results in male mice were in line with those of Chiang et al, 19 who also reported a reduction in Tb.BV in male mice with osteoblast-targeted AR inactivation. However, differing from their results, we did not detect significant differences in cortical bone thickness in male mice.…”
Section: Discussionsupporting
confidence: 93%
“…Inactivation of the AR DNA-binding activity in osteocalcinexpressing cells 19 and in collagen-1-synthesizing osteoblasts 20 has been shown to reduce trabecular bone volume in male mice. In cortical bone various effects have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…(27) Our findings suggest that this age-related decline in trabecular integrity is enhanced by inactivation of the AR in osteocytes, in line with results from previous mice models. (12,13) Studies using the col2.3Cre AR-knockout mice and osteocalcin Cre ARknockout mice also demonstrated that an inactivation of the DNA binding-dependent functions of the AR, specifically in mature osteoblasts of male mice, increases bone resorption and reduces structural integrity of the bone, leading to a similar acceleration of the age-related reduction in trabecular bone volume. (12,13) Expanding the findings of these studies, our current data support the concept that, for the maintenance of the trabecular network after puberty, a functional AR is not only required at the osteoblast stage but also at the osteocyte stage.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, previous models inactivating the AR at earlier stages of the osteoblast did not observe a significant difference in cortical structure, but mechanical properties were not documented. (12,13) The absence of a major cortical phenotype across a number of similar mice models contrasts with the significant cortical phenotype characterized by reduction of periosteal expansion observed in the ubiquitous ARKO model. (5) Puberty appears to be a critical period for the development of skeletal sexual dimorphism as characterized by wider and longer bones in male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation